Effects of Choline on Neutrophil Function and Inflammation in Growing Cattle with Modulated Methyl Group Status - M. S. Grant; H. D. Aufdemberge; B. J. Bradford; L. K. Mamedova; E. C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:This study was conducted to evaluate the effects of supplemental choline in combination with guanidinoacetic acid or creatine on immune cell function and inflammation in growing cattle. Study Description:Six ruminally-cannulated Holstein steers (321 lb) were utilized in an experiment where each steer received each of six treatments. Treatments were given via abomasal infusion of a 0 or 5 g/day of supplemental choline, and either a saline solution (control); 15 g/day guanidinoacetic acid; or 16.8 g/day of creatine, with all treatment combinations represented. Steers were fed a corn-based diet. Blood was collected during each period to measure neutrophil function, plasma haptoglobin, and plasma antioxidant potential. Bottom line:Supplementing steers with 5 g/day of choline tended to reduce plasma haptoglobin concentrations, suggesting that choline reduced systemic inflammation.
Keywords: methyl groups; choline; immune function